2000
DOI: 10.1002/hep.510310307
|View full text |Cite
|
Sign up to set email alerts
|

Cause of portal or hepatic venous thrombosis in adults: The role of multiple concurrent factors

Abstract: According to a recent hypothesis, venous thrombosis results from the concurrence of several factors. This hypothesis was assessed in patients with portal or hepatic venous thrombosis by simultaneously investigating most of the currently identified prothrombotic disorders, local precipitating factors, and other risk factors such as oral contraceptive use. Patients with a tumorous obstruction and patients with cirrhosis with portal vein thrombosis were excluded. The prothrombotic disorders that were investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
499
6
24

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 627 publications
(573 citation statements)
references
References 24 publications
(28 reference statements)
21
499
6
24
Order By: Relevance
“…On the one hand, the results presented here are in contrast with data published by Seixas et al (1997) and UttenreutherFischer et al (1997) for children with PVT, neither identifying the factor V G1691A as a common risk factor in their cohorts. On the other hand, our data are in accord with very recently published adult series of cases with portal vascular occlusion demonstrating that prothrombotic disorders, especially defects within the protein C pathway, contributed to this rare thrombotic manifestation in the patients investigated (Denninger et al, 2000;Egesel et al, 2000). Thus, we suggest that this difference in the aetiology of childhood PVT with respect to genetic prothrombotic risk factors is mainly as a result of the system of patient recruitment, different childhood age populations, and the inclusion or exclusion of catheter-related thrombosis that, in two prospective studies, has been shown not to be commonly associated with a risk of PVT in sick neonates (Schwartz et al, 1997;Guimaraes et al, 1998).…”
Section: Risk Factorssupporting
confidence: 92%
“…On the one hand, the results presented here are in contrast with data published by Seixas et al (1997) and UttenreutherFischer et al (1997) for children with PVT, neither identifying the factor V G1691A as a common risk factor in their cohorts. On the other hand, our data are in accord with very recently published adult series of cases with portal vascular occlusion demonstrating that prothrombotic disorders, especially defects within the protein C pathway, contributed to this rare thrombotic manifestation in the patients investigated (Denninger et al, 2000;Egesel et al, 2000). Thus, we suggest that this difference in the aetiology of childhood PVT with respect to genetic prothrombotic risk factors is mainly as a result of the system of patient recruitment, different childhood age populations, and the inclusion or exclusion of catheter-related thrombosis that, in two prospective studies, has been shown not to be commonly associated with a risk of PVT in sick neonates (Schwartz et al, 1997;Guimaraes et al, 1998).…”
Section: Risk Factorssupporting
confidence: 92%
“…The overall mortality in chronic onset PVT is less than 10% 8,113 whereas in cirrhosis and malignancy, it is 26%. 17 A multivariate analysis done on determinants of survival in extra hepatic portal vein thrombosis showed that advanced age, malignancy, cirrhosis, mesenteric vein thrombosis, absence of abdominal inflammation, serum levels of aminotransferase and albumin are associated with reduced survival and not to complications of portal hypertension.…”
Section: Chronic Portal Vein Thrombosismentioning
confidence: 98%
“…In upto 80% cases the underlying cause is identified when rigorously searched for. [8][9][10][11][12][13] In some cases multiple prothrombotic factors may be associated in the development of PVT. [14][15][16] In one study one or more risk factors namely prothrombotic state or abdominal inflammation was present in 87% of patients.…”
Section: Acute Non-cirrhotic Portal Vein Thrombosis Procoagulant Statementioning
confidence: 99%
See 2 more Smart Citations